Regulation of claudin/zonula occludens-1 complexes by hetero-claudin interactions - Barbara Schlingmann (Nature Portfolio, 2016)
Alcohol abuse is a risk factor for acute respiratory distress syndrome, flooding of the lungs due to compromised barrier function. Here the authors report that alcohol upregulates claudin-5 that is then recruited to tight junctions in alveolar epithelial cells, causing the displacement of claudin-18 from ZO-1 and diminished barrier function.